PERANCANGAN MAINTENANCE SCORECARD DALAM PENILAIAN KINERJA MAINTENANCE PADA PRODUKSI GLASS BLOCK - Wijaya, Levina Halim; Ahmad; Salomon, Lithrone Laricha (Universitas Tarumanagara, 2025)
Maintenance management is crucial to a company's success. PT XYZ is a glass manufacturing company that produces various types of glass. The company faces high downtime issues, especially in one of its production plants, that is glass block production. Machine breakdowns frequently halt the production process, leading to inefficiencies in various aspects. Therefore, an evaluation of the maintenance system is needed. The methods used in this study are SWOT analysis, Maintenance Scorecard, and AHP method. The SWOT analysis placed the company in quadrant 4 and identified 16 matrix strategies. The Maintenance Scorecard framework produced 20 KPIs to asses maintenance performance. The overall maintenance performance score was 84.73%. AHP method was employed to identify KPIs that should be prioritized. The five KPIs with the highest weight are: Number of Work Accidents, Quality Rate, Patrol Check, Production Efficiency, and Budget Realization. The five KPIs with the largest gaps between actual performance and targets are: Ratio of Overtime to Normal Working Hours, Loss Glass, Number of Work Accidents, Overtime Cost Index, and Quality Rate.